(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
In the formation of the meaning of linguistic signs, the reflection of human activity, the results of his social experience, of course, is more evident in the content of the subject and other fully meaningful words. However, I do not dare to say that other types of lexical units (including deictics) have no lexical meaning. Every linguistic unit has, of course, a lexical meaning. Deictic characters, including rhymes, are no exception.